Effect of Tm2O3 concentration and hydroxyl content on the emission properties of Tm doped silicate glasses - Wang, Xin; Li, Kefeng; Yu, Chunlei; Chen, Danping; Hu, Lili (Journal of luminescence, 2014)
Tm2O3-doped multi-component silicate glasses without alkali ions are prepared using a conventional melt quenching method. The Judd–Ofelt theory is applied to calculate the intensity parameters of the resultant glass. The intensity parameters of silicate glasses without alkali ions are larger than those of silicate glasses with alkali ions. The spontaneous radiation probability of the transition from 3F4 to 3H6 of glasses without alkali ions is 191.89s−1, which is larger than that of glasses with alkali ions. Moreover, the measured lifetime of the 3F4 energy level of glasses is larger too. Emission cross section results show a maximum value 3.89×10−21cm2 at 1882nm. These findings indicate that the glass in this study can be used to realize ~2μm lasers. The effect of variations in Tm2O2 concentration on the emission properties is also studied. Cross-relaxation and emission intensity enhance with increasing Tm2O3 content. However, the lifetime of the 3F4 level decreases because of concentration quenching. The influence of OH groups on the emission properties is also investigated. •Tm2O3 doped silicate glass with no alkali ions is reported.•Radiative properties has been determined using the Judd–Ofelt theory.•Effect of Tm2O3 concentration on emission properties is studied.•Influence of hydroxyl groups on emission properties is investigated.